RUANG BRAILLE SEBAGAI PENYEDIA KOLEKSI BAGI PEMUSTAKA TUNANETRA DALAM MENCARI INFORMASI DI PERPUSTAKAAN GRHATAMA PUSTAKA YOGYAKARTA - Khairunnisa, Tiara (JIMR : Journal Of International Multidisciplinary Research, 2024)
The title of the research is Braille rooms is a the collection for information by blind users Grhatama Pustaka Yogyakarta. This research aims to determine the utilization efforts made by the Grhatama Pustaka Yogyakarta DPAD Library Service Center library in providing Braille space for visitors who are blind. This research method uses a qualitative case study approach. The data source studied is the result of direct observations in the field, namely in the Ghratama Pustaka Braille Room at the DPAD DIY Library Service Hall. Meanwhile, this data collection technique uses direct observation, interviews, and documentation approaches. Then the data is processed so as to find the results / conclusions. The results of the study show that the collection of Braille rooms is a source of information that is needed and utilized by blind users.